2012
DOI: 10.1136/postgradmedj-2011-130069
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in men with type 2 diabetes

Abstract: Sexual dysfunction (SD) is common in type 2 diabetic men, but few subjects are diagnosed and treated. The prevalence of diabetes mellitus is increasing worldwide. It is expected that the number of subjects suffering from SD increases in the near future. Most studies of SD in diabetic men have focused on erectile dysfunction. There is a dearth of studies in the area of the other forms of SD. SD has consequences on the psychological well-being and reproductive function. They can be the first symptom of comorbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 112 publications
0
41
2
2
Order By: Relevance
“…DM is a medical problem which has its great implications on male sexual function [3,4]. The current study is a retrospective survey which evaluated the prevalence of different SDs as selfreported by a cohort of diabetic men who consulted directly an andrology public clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM is a medical problem which has its great implications on male sexual function [3,4]. The current study is a retrospective survey which evaluated the prevalence of different SDs as selfreported by a cohort of diabetic men who consulted directly an andrology public clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Alexandria prefecture, with the prevalence of diabetes at 8%, has the second highest prevalence of diabetes among other Egyptian prefectures [1]. Diabetes is commonly associated with several sexual dysfunctions (SDs) [3,4]. Therefore, it is supposed that a significant number of Egyptian men with diabetes will suffer from different SDs.…”
Section: Introductionmentioning
confidence: 99%
“…Although PDE-5 inhibitors are often the preferred therapy for most men with vasculogenic ED, the efficacy of these drugs is decreased in diabetic patients (Isidro, 2012), prompting a need for new treatment options. It has been shown that BAY 41-2272 is a potent relaxing agent in many tissues (Priviero et al, 2005;Teixeira et al, 2006a;Toque et al, 2008) including the CC.…”
Section: Effect Of Bay 41-2272 On Penile Erection In Db/dbmentioning
confidence: 99%
“…9 Phosphodiesterase type 5 inhibitors are the preferred therapy for most men with organic erectile dysfunction who do not have a specific contraindication to their use, in particular concurrent use (and not prescribing) of cardioactive nitrates. In addition, the vascular or neuropathic damage associated with long duration of type 2 diabetes often leads to delayed ejaculation and anejaculation, which is commonly irreversible.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%